miR-675 promotes disease progression of non-small cell lung cancer via activating NF-ÎºB signaling pathway - Feng, Y.; Yang, C.; Hu, D.; Wang, X.; Liu, X. (Cellular and Molecular Biology, 2017)
Non-small cell lung cancer (NSCLC) is a major type of lung cancer significantly affected human life. Current studies have revealed potential role of miR-675 in the etiology of lung cancer. Therefore, in this study, we aimed to investigate the role of miR-675 in NSCLC cell line. We recruited 92 cases of NSCLC patients from July 2009 to February 2011 in the oncology department. Tumor and peripheral tissue was collected for miR-675 expression. NSCLC cell lines with either miR-675 over-expression or low-expression were established. Western blotting and immunofluorescence staining were used for detecting P65 and pP65 expression and translocation in the nuclei. MiR-675 expression was significantly higher in the lung cancer tissue than the peripheral normal tissue (P < 0.001). The gene expression of pP65 was also increased and decreased in cells with over-expression or low-expression of miR-675, respectively (both P < 0.05). Whereas the trend of P65 expression was on the opposite (both P < 0.05), indicating the NF-ÎºB signaling pathway was activated when miR-675 was expressed and vice versa. Immunofluorescence staining showed that more pP65 expression was clustered in the nuclei in miR-675 over-expressed cells, which further demonstrated NF-ÎºB signaling pathway activation. Increased miR-675 expression is associated with NSCLC progression through activation of NF-ÎºB signaling pathway.